2014
DOI: 10.1242/jcs.144378
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic ovarian cancer cell malignancy is increased on soft matrices through a mechanosensitive Rho/ROCK pathway

Abstract: Although current treatments for localized ovarian cancer are highly effective, this cancer still remains the most lethal gynecological malignancy, largely owing to the fact that it is often detected only after tumor cells leave the primary tumor. Clinicians have long noted a clear predilection for ovarian cancer to metastasize to the soft omentum. Here, we show that this tropism is due not only to chemical signals but also mechanical cues. Metastatic ovarian cancer cells (OCCs) preferentially adhere to soft mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 36 publications
6
95
2
Order By: Relevance
“…Following engraftment, metastatic ovarian cancer cells cultured on soft matrices were shown to have higher resistance to chemotherapeutic drugs, a mechanical tropism that was shown to be mediated by the Rho/ROCK signaling pathway (McGrail et al, 2014). These results reinforce the idea that mechanical signals are a key factor in cancer progression and chemoresistance.…”
Section: Stiffnessmentioning
confidence: 53%
See 1 more Smart Citation
“…Following engraftment, metastatic ovarian cancer cells cultured on soft matrices were shown to have higher resistance to chemotherapeutic drugs, a mechanical tropism that was shown to be mediated by the Rho/ROCK signaling pathway (McGrail et al, 2014). These results reinforce the idea that mechanical signals are a key factor in cancer progression and chemoresistance.…”
Section: Stiffnessmentioning
confidence: 53%
“…Another recent study has shown that metastatic ovarian cancer cells undergo changes in cytoskeleton organization and exhibit increased adhesion on soft microenvironments (McGrail et al, 2014). Following engraftment, metastatic ovarian cancer cells cultured on soft matrices were shown to have higher resistance to chemotherapeutic drugs, a mechanical tropism that was shown to be mediated by the Rho/ROCK signaling pathway (McGrail et al, 2014).…”
Section: Stiffnessmentioning
confidence: 99%
“…Interestingly, ovarian cancer cells were shown to present opposite responses to matrix rigidities-these cancer cells preferentially adhere to softer ECM and present an enhanced invasive phenotype when cultured on softer substrates through RHO/ROCK signaling pathways (McGrail et al, 2014). This supports the notion that multiple mechanosensing mechanisms exist among different cell types possibly due to the different mechanical environments of their tissues of origin.…”
Section: Mechanotransduction In Cancermentioning
confidence: 55%
“…These findings demonstrated the importance of substrate stiffness on ovarian cancer cell phenotype, differing metastatic potentials between cell lines, and the incorporation of the Rho/ROCK pathway in ovarian cancer mechanotransduction. 92 To evaluate the importance of investigating cellular-ECM interactions in a 3D environment, varying stiffness 3D constructs were studied by Zhang et al, 93 Loessner et al, 94 and Guo et al 95 The work of Zhang and Loessner both utilized PEG constructs. Zhang et al investigated hydrogels with three stiffnesses and found that the epithelial ovarian papillary serous cystadenocarcinoma cell line, 96 HO8910, grew the fastest, formed multicellular spheroids, and adhered preferentially to the medium hydrogel stiffness, of 12 kPa.…”
Section: Ecm Stiffness Within the Ovarian Cancer Mechanical Microementioning
confidence: 99%
“…101,102 As ovarian cancer experiences an environment with variable stiffness, the YAP/TAZ pathway is a point of interest for future mechanotransduction studies. The Rho/ Rock pathway has already been tied to stiffness effects on ovarian cancer cells 92 and it has been established as a well-known factor in both mechanotransduction and cancer progression for a variety of tumor types. [103][104][105][106][107] Caveolin-1 has been shown to be essential for stiffness sensing, and thus when silenced, tumor cells are able to proliferate and migrate independent of the rigidity of the surrounding ECM.…”
Section: Ecm Stiffness Within the Ovarian Cancer Mechanical Microementioning
confidence: 99%